2010
DOI: 10.1063/1.3474574
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study of the zero-field splitting in high-spin nitrenes

Abstract: This work presents a detailed evaluation of the performance of density functional theory (DFT) for the prediction of zero-field splittings (ZFSs) in high-spin nitrenes. A number of well experimentally characterized triplet mononitrenes, quartet nitrenoradicals, quintet dinitrenes, and septet trinitrenes have been considered. Several DFT-based approaches for the prediction of ZFSs have been compared. It is shown that the unrestricted Kohn-Sham and the Pederson-Khanna approaches are the most successful for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…The most realistic theoretical estimation of E Q in dinitrene 16 is obtained from PBE/DZ calculations of the spin–spin interaction parameter E Q SS (Table 3). This fact indicates that the contribution of the spin–orbit interactions to the total parameter E Q of dinitrene 16 is quite small, as is typical for most of quintet dinitrenes [32]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most realistic theoretical estimation of E Q in dinitrene 16 is obtained from PBE/DZ calculations of the spin–spin interaction parameter E Q SS (Table 3). This fact indicates that the contribution of the spin–orbit interactions to the total parameter E Q of dinitrene 16 is quite small, as is typical for most of quintet dinitrenes [32]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of nitrenes 6a – c have shown that the most accurate theoretical evaluations of D S and E S by the DFT approach were obtained by using the PBE and BLYP functionals in combination with the DZ or EPRII basis sets [32]. Extensive DFT calculations performed in the present work show that the best agreement between the experiment and theory is observed at the BLYP/EPRII level of theory, overestimating the experimental D S and E S values of trinitrene 18 by only 6% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations